Efektivitas penggunaan bahasa suroboyoan dalam penyampaian berita pojok kampung jtv bagi masyarakat kecamatan gayungan, kota surabaya - Hutomo, Dendy Prasetyo; Jusnita, Raden Ayu Erni (Universitas Dr.Soetomo, 2020)
Corner Village is a program from one of the local television channels, JTV, which is the most controversial and famous since it was first aired. The program uses Suroboyoan Language which is known as an inappropriate language educatively. Even so, Kampung Corner's rating is still high. The purpose of this study was to measure the effectiveness of the use of the Suroboyoan Language in the delivery of the Pojok Kampung JTV news as information on the community of Gayungan District, Surabaya City. This type of research is quantitative research. The total population of this study was 25,937 people. Then determine the sample with the Slovin formula in order to obtain a sample of 100 respondents. The sampling technique in this study used random sampling. In this study data collection was done by questionnaire technique. Data analysis techniques are done by simple tabulation, coding, editing. The results of this study are that the use of the Suroboyoan Language in the Pojok Kampung News Program has been considered effective by the research respondents who are spectators of the Pojok KampungNews program. This can be seen from measurements using the EPIC method, namely empathy, persuasion, impact, and communication.Keywords: suroboyoan language, news submission, pojok kampung.